Meet Up Buddy Up: effective strategies to promote 4th grade students' intergroup prosocial behavior - Xiao, Sonya Xinyue; Ren, Haining; Hanish, Laura D.; Miller, Cindy Faith; Martin, Carol Lynn; Fabes, Richard A. (Frontiers in Developmental Psychology, 2023)
Given the changing demographics in the U.S., it has become increasingly important to promote prosocial behavior toward those dissimilar from oneself. This research is the first to examine the degree to which children’s group-based prosocial behavior, specifically, prosocial behavior directed to other-gender peers, can be promoted through simple classroom-based intervention strategies. Using a randomized controlled trial (RCT) pre- and post-design with 346 4th graders from four schools in the Southwest over one academic year, we examined the effect of implementing simultaneously two strategies for promoting relationships among diverse peers, Meet Up and Buddy Up (MUBU). MU involved promoting group/classroom level peer interactions whereas BU focused on dyadic peer interactions. Path analysis yielded support for our hypothesis that MUBU effectively increased children’s other-gender prosociality above and beyond baseline prosociality. The finding speaks to the utility of relationship-building for enhancing children’s intergroup prosocial behavior. We discussed implications for research and educational practices.